2022
DOI: 10.7554/elife.70164
|View full text |Cite
|
Sign up to set email alerts
|

Environmental selection overturns the decay relationship of soil prokaryotic community over geographic distance across grassland biotas

Abstract: Though being fundamental to global diversity distribution, little is known about the geographic pattern of soil microorganisms across different biotas on a large scale. Here, we investigated soil prokaryotic communities from Chinese northern grasslands on a scale up to 4,000 km in both alpine and temperate biotas. Prokaryotic similarities increased over geographic distance after tipping points of 1,760 - 1,920 km, generating a significant U-shape pattern. Such pattern was likely due to decreased disparities in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
(140 reference statements)
0
4
2
Order By: Relevance
“…It was noted in this study that despite the significant influence of different microhabitats on shaping microbial communities, they all displayed consistent biogeographic patterns (Figure 3), indicating the presence of shared environmental drivers that shape microbial community composition. Contrasting with our findings, several other studies reported that specific microbial communities — such as subsoil prokaryotes (Zhang et al, 2022), soil archaea (Pasternak et al, 2013), soil fungi (Xing et al, 2021), root‐associated fungi (Queloz et al, 2011), and phyllosphere bacteria (Wei et al, 2022)—did not exhibit significant correlations with geographic distance. These contrasting findings indicate that the biogeographic patterns of plant‐associated microbial communities can vary depending on the specific microbial group, environmental conditions, and geographical context.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was noted in this study that despite the significant influence of different microhabitats on shaping microbial communities, they all displayed consistent biogeographic patterns (Figure 3), indicating the presence of shared environmental drivers that shape microbial community composition. Contrasting with our findings, several other studies reported that specific microbial communities — such as subsoil prokaryotes (Zhang et al, 2022), soil archaea (Pasternak et al, 2013), soil fungi (Xing et al, 2021), root‐associated fungi (Queloz et al, 2011), and phyllosphere bacteria (Wei et al, 2022)—did not exhibit significant correlations with geographic distance. These contrasting findings indicate that the biogeographic patterns of plant‐associated microbial communities can vary depending on the specific microbial group, environmental conditions, and geographical context.…”
Section: Discussioncontrasting
confidence: 99%
“…It was noted in this study that despite the significant influence of different microhabitats on shaping microbial communities, they all displayed consistent biogeographic patterns (Figure 3), indicating the presence of shared environmental drivers that shape microbial community composition. Contrasting with our findings, several other studies reported that specific microbial communitiessuch as subsoil prokaryotes (Zhang et al, 2022), soil archaea (Pasternak et al, 2013), soil fungi (Xing et al, 2021), rootassociated fungi (Queloz et al, 2011) The results revealed that the α-diversity and richness of leaf microbiomes exhibit greater variation across geographic distances than belowground microbiomes, specifically root and soil microbiomes (Figure 3; Tables S10 and S11). Clearly, compared to leaf microbiomes, subterranean microbiomes experienced localized conditions that result in a weaker distance-decay relationship (Figure 3).…”
Section: The Distance-decay Patterns Of Plantassociated Microbiomescontrasting
confidence: 99%
“…Notably, environmental heterogeneity, rather or better than environmental variables themselves, was responsible for the bacterial spatial turnover rates, especially the heterogeneity of soil pH or SWC. Effects of soil pH and SWC on the composition or spatial pattern of soil bacteria have been proved in previous studies (Li et al, 2017;Shen et al, 2013;Tripathi et al, 2018;Zhang et al, 2022). According to the habitat heterogeneity hypothesis, increased heterogeneity with an amplified area is the most common explanation for taxa-area patterns in the literature for the specificity of taxa in different habitats (Horner-Devine et al, 2004;Hubbell, 2001;Schuler et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Parameter estimation was rigorously performed by maximum-likelihood using the sampling formula developed by Etienne (Etienne et al, 2006;Etienne & Olff, 2005). This model is considered as a potentially useful null model in ecology; in this model, the species relative abundances in a guild are determined by two parameters, namely, θ and m. The θ governs the appearance of a new species in the regional species pool, and m governs immigration into local communities of individuals from the regional species pool (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Homogeneous selection and homogenizing dispersal were the two most important assembly processes along the elevational gradient in Daiyun mountain (Figure 3a,c), corresponding to our first hypothesis. The habitat at small spatial scales can only sustain a limited number of individuals [17], and since homogeneous selection and homogenizing dispersal can reduce β diversity [63,64], we speculate that microbial community along the elevational gradient of Daiyun mountain may exhibit lower β diversity. Biotic factors play an important role in microbial community assembly [3].…”
Section: Mechanisms For the Soil Microbial Community Assemblymentioning
confidence: 97%